Feedback Techniques Used by the Basic Level Teachers in Teaching Free Writing - Kandel, Tara Prasad (Journal of Gurubaba, 2025)
The descriptive survey research entitled Feedback techniques used by the basic level teachers in teaching free writing is an effort to study feedback techniques used by the basic level teachers in teaching writing comprehension. The study was conducted in seven community schools of Birendranagar Municipality of Surkhet district. The study included 40 teachers and 40 students as the sample population. The study utilized one set of close ended questionnaires as the tool of data collection. The study was carried out in community basic schools of Surkhet district. The findings of the study showed that the teachers found feedback techniques used by the basic level purposeful, encouraging and joyful to their students were positive towards the feedback technique for improving student's free writing. The data obtained from close ended questions were displayed statistically. The study revealed that most of the school level teachers were disappointed with using feedback techniques in their EFL class because of the lack of resources encouragement and proper administrative support. So, it is recommended to develop fundamental of feedback skills and related basic level teachers.